1954
DOI: 10.1063/1.3061702
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Aspects of the Quantum Theory of Fields

Abstract: Part 111. Boson Field in Interaction with a Given Source Distribution Expectation Values of the Energy a d the Number of BosonsThe simplest specific problem that may be posed in field quantum theory is"to determine what happens in a field under the influence of a given source distribution. In the subsequent discussion of this problem we shall employ the Heisenberg picture, unless otherwise stated. As before, the operator which corresponds to the "field quantity" will be denoted by ," and considered as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
7

Year Published

1967
1967
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 0 publications
0
124
0
7
Order By: Relevance
“…In this section we apply the above general results to the infinite series A n , B n , C n , D n of nilpotent Lie algebras defined by the Serre relations (11) or, equivalently, (16). Let g be any such Lie algebra.…”
Section: Quantification Of the Classical Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we apply the above general results to the infinite series A n , B n , C n , D n of nilpotent Lie algebras defined by the Serre relations (11) or, equivalently, (16). Let g be any such Lie algebra.…”
Section: Quantification Of the Classical Seriesmentioning
confidence: 99%
“…In line with the main idea of our approach, the skew primitive elements must play the same role in quantum enveloping algebras as the primitive elements do in the classical case. By the Friedrichs criteria [13], [16], [32], [34], [35], the primitive elements form the ground Lie algebra in the classical case. For this reason we consider the space spanned by the skew primitive elements and equipped with the quantum Lie operations as a quantum analogue of a Lie algebra.…”
Section: Introductionmentioning
confidence: 99%
“…(See [8] for a reprint.) Among the representations which he studied, he found only the standard zero-interaction (Fock) representation to have a number operator.…”
Section: Introductionmentioning
confidence: 99%
“…condition is well known. It dates back to semirigorous work of Friedrichs in the early fifties [7]. The first rigorous proof of an equivalent condition in the boson case is due to Shale [l I], in the fermion case to Shale and Stinespring [12].…”
Section: Formulation In Terms Of Unitary and Pseudo-unitary Operatorsmentioning
confidence: 99%
“…In this form the transformation has been applied by many authors to solid-state physics, statistical mechanics, and relativistic quantum field theory, in particular the external field problem. Purely mathematical studies using this formalism can be found in the books by Friedrichs [7] and Berezin [3], and in [8]. One introduces new annihilation and creation operators where Tl and T, are complex-linear operators on Z+ , such the CAR (CCR), i.e., such that (2.24) that the ?…”
Section: Preliminariesmentioning
confidence: 99%